Assessment of the potential use of MALDI-TOF MS for the identification of bacteria associated with chilled vacuum-packaged lamb meat. (July 2021) - Altakhis, Mohammed; Pillidge, Christopher J.; Osborn, A. Mark; Torley, Peter J.; Kaur, Mandeep
Abstract: The focus of this study was to compare the effectiveness of MALDI-TOF MS and partial 16S rRNA gene sequencing for the identification of bacteria isolated from VP lamb meat stored chilled at 5 °C for 21 days, at the same time gaining insights into bacterial changes over time. The identity of bacterial isolates on non-selective and selective agars was determined by both methods and results compared. Results showed that total bacterial numbers increased over the 21 days (as expected) with Staphylococcus and Pseudomonas (day 0) being replaced by Carnobacterium, Brochothrix and members of the Enterobacteriaceae family by day 21. A high level of agreement (86–100%) for bacterial isolates' identity at genus level was observed between MALDI-TOF MS and partial 16S rRNA gene-based sequencing for isolates where identification was possible. With its cheaper cost and faster turnaround time, once optimized, MALDI-TOF MS could become a useful alternative to 16S rRNA gene-sequencing for the rapid identification of red meat bacterial isolates.